Hearts, strings, and other breakable things - Firkins, Jacqueline (2019)
Living with her aunt's family in Mansfield, Massachusetts, for a few months before turning eighteen and starting college, Edie is torn between Sebastian, the boy next door, and playboy Henry.
Keywords: Dating -- Fiction; Family life -- Fiction; Cousins -- Fiction; Private schools -- Fiction; Schools -- Fiction; Massachusetts -- Fiction